2019
DOI: 10.5812/ijp.81353
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Social Support and Perceived Stress in the Mothers of Infants with Colic

Abstract: Background: High stress levels in the parents of infants with colic have negative impacts on their quality of life. Maternal concerns with infants' needs can be reduced through social support. Objectives: The aim of this study was to assess the relationship between social support and perceived stress in the mothers of infants with colic. Methods: This cross-sectional study was carried out on 200 mothers of infants with colic referred to 14 healthcare centers affiliated to Iran University of Medical Sciences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Since the nurses probably don't have sufficient time to meet the parents' emotional needs, applying the members of volunteer supportive teams can be suitable. [ 37 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since the nurses probably don't have sufficient time to meet the parents' emotional needs, applying the members of volunteer supportive teams can be suitable. [ 37 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggest that reassuring parents (that the problem will be resolved by 3-4 months of age without any serious long-term effect), providing social support, and reducing stress levels are the most effective ways to manage infantile colic. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Researchers suggest that reassuring parents (that the problem will be resolved by 3-4 months of age without any serious long-term effect), providing social support, and reducing stress levels are the most effective ways to manage infantile colic. 9 The assessment of colic is quite complicated. Given the ambiguous nature of colic, only a few tools have been made for the assessment and diagnosis of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, some studies have indicated a significant maternal role in the management of infantile colic. For instance, the positive effects of social support and spousal assistance in the management and caretaking of colic babies have been described in a cross-sectional Iranian study [ 16 ]. Moreover, a study enrolling more than 200 Turkish mothers revealed that the majority (more than 60%) of mothers used behavioral coping mechanisms such as rocking, holding and messaging baby bellies and feet to manage infantile colic during 1-6 months of age [ 17 ].…”
Section: Introductionmentioning
confidence: 99%